Risk factors for long-term hip osteoarthritis in patients with hip dysplasia without surgical intervention. Issue 1 (19th January 2022) - Melugin, Heath P; Hale, Rena F; Lee, Dustin R; LaPrade, Matthew D; Okoroha, Kelechi R; Sierra, Rafael J; Trousdale, Robert T; Levy, Bruce A; Krych, Aaron J
ABSTRACT: Hip dysplasia is a common cause of hip pain and a known risk factor for hip osteoarthritis (OA) and early total hip arthroplasty (THA). Unfortunately, little is known about the specific factors associated with an increased risk of OA. The purpose was (i) to report the overall rate of symptomatic hip OA and THA and (ii) to identify radiographic features and patient characteristics associated with the development of symptomatic hip OA. A geographic database was used to identify all patients aged 14–50 years old diagnosed with symptomatic hip dysplasia between 2000 and 2016. Kaplan–Meier analysis was used to determine the rate of symptomatic hip OA, defined as a Tönnis grade of ≥1 on hip radiograph. Univariate and multivariate proportional hazard regression models were performed to determine risk factors for OA. One hundred and fifty-nine hips (144 patients) with hip dysplasia (52 F:107 M) out of 1893 patients with hip pain were included. Of these, 45 (28%) had severe hip dysplasia with a lateral center-edge angle ≤18°. Mean age at time of presentation was 26.1 (±10.1) years. Mean follow-up time was 8.2 (±5) years. The rate of OA was 20%. THA was performed in 11% of patients. Body mass index >29 ( P  = 0.03) and increased age ( P  < 0.01) were risk factors for OA. Patients with symptomatic hip dysplasia are at significant risk of developing hip OA. Body mass index >29 and age ≥35 years at the time of presentation with hip pain were risk factors for hip OA.